Housing Contribution to Urban Regeneration - Hussaen Ali Hasan Kahachi; Wijdan Abdul Jalil (Iraqi Journal of Architecture and Planning, 2017)
this research is looking at notion of urban regeneration and housing role on it. the research is structured into two parts; the first part is concerned with defining urban regeneration, its importance, and the and the different factors in academic literature. then it continues by dividing and thoroughly analyzing/discussing the different housing contributions to urban regeneration both directly and indirectly. it will provide critical review of these contributions against future needs and changes. the second part will further evaluate all discussed in the first part in practice through a casestudy of the welsh housing quality standards (whqs) and "the can do toolkit 1 & 2" introduced by the welsh housing committee in the united kingdom in 2003, 2006 and 2008 respectively. the research will consider the links between the different contributions and possible effects it may have on the region. finally, some key points will be presented in the conclusion to highlight the different housing contributions to urban regeneration and their potential benefits and limitations.